Analisis Efektivitas dan Kontribusi Penerimaan Pajak Sarang Burung Walet Terhadap Pajak Daerah Kabupaten Kubu Raya - Wulandari, Renny (Jurnal Akuntansi, Auditing dan Investasi, 2021)
Kubu Raya Regency sets a tax on swallow nests which is regulated in Regional Regulation Number 2 of 2016 concerning Swallow's Nests Tax. This study aims to determine the level of effectiveness and contribution of swallow's nest tax revenue to local taxes and the factors that influence it. The data used are primary data (results of interviews, observations and questionnaires) and secondary data (target and realization data). The analysis in this study was carried out for the years 2012-2019, the analysis technique used a qualitative descriptive analysis method with the formula for the ratio of effectiveness and contribution as well as observation / interviews with regional tax officers at the Regional Asset Financial Management Agency. The effectiveness of swallow's nest tax revenue is still less effective with an average yield of 69.09% from 2012-2019, the contribution of swallow's nest tax revenue to local tax revenue is still very less than 2012-2019 with an average amount of 5.4 %. The factors identified that affect the effectiveness and contribution are administration, market price of swallow's nest, number of taxpayers, willingness and awareness to pay taxes, location of taxpayers and inadequate database. Keywords: Regional Regulation, Local Tax, Swallow's Nest Tax, Effectiveness, Contribution, in the Regional Asset Financial Management Agency of Kubu Raya Regency.